Descriptions of three new species of Odonata from Brazil - Costa, Janira M.; de Souza, Luiz O.i.; Muzón, Javier (Zootaxa, 2006)
Three new species are described here: Oxyagrion zielmae sp. nov. (Coenagrionidae) from one male collected at Costa Rica, Mato Grosso do Sul state; Lestes fernandoi sp.nov. (Lestidae) from a pair from Imperatriz, Maranhão state and Perithemis capixaba sp. nov. (Libellulidae) from one male from Mutum Preto, Espírito Santo state, all deposited at Museu Nacional, Rio de Janeiro, Brazil. Oxyagrion zielmae is similar to O. pavidum Selys, 1876 but differs by having cerci and paraprocts the same size, pterostigma long and narrow and terminal segment of genital ligula with the two lobes larger than in O. pavidum. Lestes fernandoi is compared with L. auritus Hagen in Selys, 1862; L. bipupillatus Calvert, 1909; L. dichrostigma Calvert, 1909; Lestes falcifer Sjöstedt, 1918; L. forficula Rambur, 1842; L. minutus Selys, 1862 and L. paulistus Calvert, 1909. The new species is most similar to Lestes falcifer and L. paulistus, but differ by the peculiar color of pterothorax, caudal appendages and genital ligula. Perithemis capixaba is similar to P. mooma Kirby, 1889 but differs by having the first segment of vesica spermalis slowly rounded, in P. mooma this structure is trapezoidal. Illustrated keys to new species are included.